Mycobacterium avium Subspecies paratuberculosis Drives an Innate Th17-Like T Cell Response Regardless of the Presence of Antigen-Presenting Cells - DeKuiper, Justin L.; Cooperider, Hannah E.; Lubben, Noah; Ancel, Caitlin M.; Coussens, Paul M. (Frontiers in Veterinary Science, 2020)
The gastrointestinal disease of ruminants is clinically known as Johne's disease (JD) and is caused by Mycobacterium avium subspecies paratuberculosis (MAP). An accumulative effect by insensitive diagnostic tools, a long subclinical stage of infection, and lack of effective vaccines have made the control of JD difficult. Currently lacking in the model systems of JD are undefined correlates of protection and the sources of inflammation due to JD. As an alternative to commonly studied immune responses, such as the Th1/Th2 paradigm, a non-classical Th17 immune response to MAP has been suggested. Indeed MAP antigens induce mRNAs encoding the Th17-associated cytokines IL-17A, IL-17F, IL-22, IL-23, IL-27, and IFNγ in CD3+ T cell cultures as determined by RT-qPCR. Although not as robust as when cultured with monocyte-derived macrophages (MDMs), MAP is able to stimulate the upregulation of these cytokines from sorted CD3+ T cells in the absence of antigen-presenting cells (APCs). CD4+ and CD8+ T cells are the main contributors of IL-17A and IL-22 in the absence of APCs. However, MAP-stimulated MDMs are the main contributor of IL-23. In vivo, JD+ cows have more circulating IL-23 than JD– cows, suggesting that this proinflammatory cytokine may be important in the etiology of JD. Our data in this study continue to suggest that Th17-like cells and associated cytokines may indeed play an important role in the immune responses to MAP infection and the development or control of JD.